Sex therapy in a couple with learning disabilities - Bell, D; Toplis, L; Espie, C (1999)
Despite greater emphasis in the last decade on sex education programmes for young people who have learning disabilities, there are few reports of sexual counselling or sex therapy. This case study discusses a married couple who had been married for seven months and who had been together for the previous year. Sexual intercourse had only been achieved on two occasions. This was too low in frequency for both partners. No other problems, such as lack of time in foreplay or insufficient enjoyment ofthe act itself was mentioned, at this time, by either partner. On the two occasions of sexual intercourse, both partners stated that they had reached orgasm. There were no indications of any difficulties in either partner's sexual history (such as abuse), and their knowledge of sexual matters met the standards of routine education packages for people with learning disabilities. A number of standard measures were amended and used to assess current functioning and to chart progress. For treatment, an approach in two phases was used.